2022
DOI: 10.1093/jbi/wbac063
|View full text |Cite
|
Sign up to set email alerts
|

The Dense Breast Clinic: Initial Experience of a Patient-Centered Breast Imaging Clinic

Abstract: Objective Establish a radiologist-run consultation clinic to review breast density and supplemental screening exams (SSEs) directly with patients in response to breast density reporting laws. Methods Breast radiologists opened and staffed a clinic for formal patient consultations regarding breast density and SSEs. An IRB-approved questionnaire assessed patient knowledge of breast density, SSEs, and encounter satisfaction. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Websites [ 35 ] and factsheets [ 36 ] that provide breast density information should be aware of these common misconceptions and actively seek to dispel them. For the most comprehensive information, personalised counselling within a dedicated radiologist-run breast density consultation may foster better understanding among women about breast density and augment their participation in shared decision-making [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Websites [ 35 ] and factsheets [ 36 ] that provide breast density information should be aware of these common misconceptions and actively seek to dispel them. For the most comprehensive information, personalised counselling within a dedicated radiologist-run breast density consultation may foster better understanding among women about breast density and augment their participation in shared decision-making [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it may be beneficial to develop partnerships between primary care and radiology to help counsel women on appropriate supplemental screening and/or preventive measures. 62 In summary, future laws or regulations involving breast density notifications should ensure that communications promote a more comprehensive understanding of breast cancer risk to inform choices about screening and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A review of interventions involving the use of risk assessment tools in primary care concluded that more comprehensive interventions that combined risk assessment with decision support were more likely to have an effect on behavior. In some cases, it may be beneficial to develop partnerships between primary care and radiology to help counsel women on appropriate supplemental screening and/or preventive measures . In summary, future laws or regulations involving breast density notifications should ensure that communications promote a more comprehensive understanding of breast cancer risk to inform choices about screening and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Websites (35) and factsheets (36) that provide breast density information should be aware of these common misconceptions and actively seek to dispel them. For the most comprehensive information, personalised counselling within a dedicated radiologist-run breast density consultation may foster better understanding among women about breast density and augment their participation in shared decisionmaking (37).…”
Section: Discussionmentioning
confidence: 99%